Nutritional and Socioeconomic Determinants of Overweight and Obesity in the French Amazon: The Health Barometer Study - Massicard, Mickael; Drak Alsibai, Kinan; Nacher, Mathieu; Sabbah, Nadia (Frontiers in Endocrinology, 2022)
Objectives: French Guiana is a multicultural overseas territory where obesity is a major public health problem. This study aimed to highlight the nutritional and socioeconomic determinants of overweight and obesity in different populations in French Guiana. Methods: A two-stage random sample of 1390 individuals aged 30 to 75 years was surveyed by telephone, and the participants were initially screened for diabetes. Logistic regression was fitted on the sample to adjust for potential confounding factors. Results: Overweight and obesity were foundin 54.7% of the respondents, a higher proportion than in mainland France. There was a significant body image discrepancy in our population, with a higher risk of obesity among single women, often immigrantsfrom the non-French Caribbean and South America, unemployed or low education. Conclusions: The main factors associated withobesity werebeing a precariousness immigrant; there was often a mismatch between body image and overweight/obesity,which is a major obstacle to the improvement of dietary behaviorsand lifestyle. This information provides operational clues as to where to act and the necessary adaptations to attempt to modify behaviors in a culturally-adapted manner.